2021
DOI: 10.3389/fpsyg.2021.725132
|View full text |Cite
|
Sign up to set email alerts
|

Using Assessment for Learning: Multi-Case Studies of Three Chinese University English as a Foreign Language (EFL) Teachers Engaging Students in Learning and Assessment

Abstract: Student engagement is an important issue in learning and teaching given its positive effects on students' learning outcomes. Assessment for Learning (AfL), an assessment and pedagogic innovation, if done well, can fully engage students in the learning and assessment process. Adopting a multi-case design, the present study explored how Chinese university English as a Foreign Language (EFL) teachers used AfL to facilitate student engagement in their classrooms and what factors influenced their AfL practices. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
(112 reference statements)
2
16
0
Order By: Relevance
“…With respect to the limited number of studies that have focused on university level students (e.g., Liu, 2002 ; Zheng et al, 2007 ; Wang, 2016 ; Wu et al, 2021c ), Liu’s (2002) study appears to be the first one using self-assessment in the English writing classes. Findings of Liu’s study suggested that Chinese university students’ self-assessment reliability appeared to be affected by students’ English proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the limited number of studies that have focused on university level students (e.g., Liu, 2002 ; Zheng et al, 2007 ; Wang, 2016 ; Wu et al, 2021c ), Liu’s (2002) study appears to be the first one using self-assessment in the English writing classes. Findings of Liu’s study suggested that Chinese university students’ self-assessment reliability appeared to be affected by students’ English proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers’ perceptions of assessment practices are deemed as significant indicators of their assessment literacy and assessment approaches ( Looney et al, 2018 ; Wu et al, 2021c ). Further, teachers’ initiatives and attitudes toward self-assessment are closely associated with the growth of student self-assessment capabilities ( Tan, 2007 ; Bourke, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assessment refers to “a process during which students collect information about their own performance, evaluate and reflect on the quality of their learning process and outcomes according to selected criteria to identify their own strengths and weaknesses” ( Yan and Brown, 2017 , p. 1248). In the self-assessment process, students are encouraged to take responsibility for their learning by acting as not only recipients of assessment but also designers and users of assessment ( Wu et al, 2021b ). Therefore, self-assessment is a learning process, rather than an assessment method, that provides students with ample learning opportunities ( Yan and Carless, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, with the accelerated pace of economic development and opening-up, the Chinese Ministry of Education (MoE) launched a new round of curriculum reform nationwide to meet the challenges of globalization. The Outline of the National Medium and Long-Term Education Reform and Development Plan (2010–2020) made it clear that the country has an increasing demand for employees with high levels of foreign language competence ( Chen et al, 2021 ; Liu et al, 2021 ; Wu et al, 2021 ), in particular, English language proficiency, considering English as a lingua franca ( Kecskes, 2019 ). Thus, a higher bar has been set for foreign language education and a distinct orientation toward developing students’ communicative competence and intercultural literacy can be found in MoE’s goal statements.…”
Section: Introductionmentioning
confidence: 99%